Relation of Serum Phosphorus Levels to Carotid Intima–Media Thickness in Asymptomatic Young Adults (from the Bogalusa Heart Study) - Ruan, Litao; Chen, Wei; Srinivasan, Sathanur R.; Xu, Jihua; Toprak, Ahmet; Berenson, Gerald S. (The American journal of cardiology, 2010)
Increased serum phosphorus has been associated with increased mortality from cardiovascular (CV) disease. However, information is scant regarding the influence of serum phosphorus within the normal range on vascular risk in subclinical atherosclerosis in asymptomatic young adults. Serum phosphorus and other CV risk factor variables were measured in 856 white and 354 black subjects without known CV disease or renal disease. Carotid intima–media thickness (IMT) was measured by B-mode ultrasonography. Significant race and gender differences were noted for serum phosphorus (blacks > whites) and carotid IMT (black women > white women; men > women). In bivariate analyses, serum phosphorus was correlated with carotid IMT (p <0.001), and smokers showed higher phosphorus levels than nonsmokers (p = 0.008). In multivariate regression analyses, carotid IMT was significantly associated with serum phosphorus (regression coefficient beta = 0.028, p <0.001) and smoking (beta = 0.032, p <0.001), adjusting for other CV risk factors and estimated glomerular filtration rate. In addition, a significant interaction effect of cigarette smoking and serum phosphorus on carotid IMT was noted, with a greater increasing trend of carotid IMT with phosphorus in smokers than in nonsmokers (p = 0.019 for interaction). In conclusion, serum phosphorus within the normal range is an important correlate of carotid IMT in asymptomatic young adults, with smoking potentiating this adverse association.